Anopheles mosquitoes: not just flying malaria vectors… especially in the field - Boete, C (Trends in parasitology, 2009)
The polymorphism of genes involved in the immunity of malaria vectors has been the subject of several recent studies with mosquitoes from natural populations. Most of the genes examined are known for their role against Plasmodium berghei and not necessarily for their role against Plasmodium falciparum. It seems, therefore, to be highly important not only to be cautious when linking natural selection with malaria epidemiology but also to consider the importance of other parasites and the environment on the mosquito genome.